Personalised Learning Platform Using AI-Based Adaptive Systems - B, Shashi S; S, Raghunandhan; Geetha, G; Mariraj, Aathityan; A, Siva Ananth; R, Prabhavathi (2025 International Conference on Innovative Trends in Information Technology (ICITIIT), 2025)
Students transitioning from 10 th to 11 th grade often face difficulties adapting to new academic challenges, including more advanced subjects and a broader syllabus. These struggles lead to a decline in academic performance and a loss of confidence. To address this, our project focuses on creating a user-friendly learning website dedicated to helping these students by offering personalized learning paths. The platform assesses individual student needs and tailors specific academic strategies to ensure they can grasp core concepts more effectively, preparing them for the increased difficulty in their 11 th -grade subjects. This solution leverages adaptive learning techniques to offer curated study plans that target weak areas while reinforcing strengths, helping students progress at their own pace. The website provides engaging multimedia resources, practice quizzes, and regular feedback to ensure continuous improvement. By focusing on making learning more accessible and personalized, the project aims to bridge the gap between the 10 th and 11 th grade, offering students a structured yet flexible approach to mastering their new curriculum and building the confidence they need for academic success.